2018
DOI: 10.1016/j.athoracsur.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 1: A Step Toward Immunoscore for Esophageal Cancer

Abstract: Positive staining for PD-L1 may be a prognostic marker for decreased survival in esophageal adenocarcinoma. Additional TIL cell types should be investigated for creation of an esophageal cancer Immunoscore. PD-L1 has potential as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…For PD-L1, a well-defined immune checkpoint marker, conflicting data exist in EAC. This is among other things due to different analysis and especially scoring methods used in the past [ 21 , 22 ]. The combined positive score (CPS) for PD-L1 was established for gastric and gastroesophageal junction adenocarcinomas serving as a predictive marker for PD1-inhibitor therapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For PD-L1, a well-defined immune checkpoint marker, conflicting data exist in EAC. This is among other things due to different analysis and especially scoring methods used in the past [ 21 , 22 ]. The combined positive score (CPS) for PD-L1 was established for gastric and gastroesophageal junction adenocarcinomas serving as a predictive marker for PD1-inhibitor therapy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical trial of SHR-1210, an anti-PD-1 antibody, Huang et al showed that PD-L1 expression was not significantly correlated with ORR in patients with EC (129). Hynes et al verified that in patients with EAC, survival outcomes were worse in patients whose tumors stained positive for PD-L1 than in patients with PD-L 1 -n e g a t i v e t u m o r s w h o u n d e r w e n t n e o a d j u v a n t chemoradiation therapy (130). In addition, Ohigashi et al observed that even in patients with ESCC, PD-L1-positive patients exhibited a poorer prognosis, and upregulation of PD-L1 was more pronounced, with worse tumor differentiation, positive lymph node metastasis, and advanced stage of ESCC (131), indicating that PD-L1 status may be a negative predictor of prognosis for patients with EC.…”
Section: Immune Checkpoint Proteinsmentioning
confidence: 99%
“…16 Similar results have also been achieved by Hynes et al in their study where PD-L1 positivity was found to be associated with significantly lower survival in specimens of patients who underwent esophagectomies for EAC. 17 More recently, Rong et al, 18 using tissue microarray and immunohistochemistry, studied PD-L1 expression on tumor cells and tumor-infiltrating cell in 378 advanced (T2-T4a) ESCC. No patient recruited had undergone neoadjuvant chemotherapy that could have changed PD-L1 exposure.…”
Section: Immunomodulation Mechanisms and Immune-checkpoint Expressionmentioning
confidence: 99%